THE INFLUENCES OF ORGANIZATIONAL CULTURE, QUALITY OF WORK LIFE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT RSPAD GATOT SOEBROTO HOSPITAL - Aktif Budiono, Nur (Dinasti International Journal of Management Science, 2021)
This research has purposed to revealed the influences of organizational culture, quality of work life and employee organizational commitment towards employee performance at RSPAD Gatot Soebroto Hospital. The survey type which conducted in this research where all the data obtained would be analyzed through path analysis after all these variables were put into correlation matrix. In this research, the RSPAD Gatot Soebroto Hospital workers will be chosen as unit analysis and 275 samples will be selected by stratified random sampling. This analysis result would be advantageous for the hospital’s management, scientists and customers or patients. Through this research, it is known that any change or difference occurring in employee performance might be caused by organizational culture, quality of work life and organizational commitment. In conclusion, organizational culture, quality of work life and organizational commitment had an impact on employee performance. Thus, the policies regarding the factors of organizational culture, quality of work life and organizational commitment need to be arranged into strategic plan of human resources management.